2002
DOI: 10.1093/brain/awf205
|View full text |Cite
|
Sign up to set email alerts
|

Abeta 17-42 in Alzheimer's disease activates JNK and caspase-8 leading to neuronal apoptosis

Abstract: The p3 peptide [amyloid beta-peptide (Abeta) 17-40/42], derived by alpha- and gamma-secretase cleavage of the amyloid precursor protein (APP), is a major constituent of diffuse plaques in Alzheimer's disease and cerebellar pre-amyloid in Down's syndrome. However, the importance of p3 peptide accumulation in Alzheimer's disease and its toxic properties is not clear. Here, we demonstrate that treatment of cells with Abeta 17-42 leads to apoptosis in two human neuroblastoma cell lines, SH-SY5Y and IMR-32. Abeta 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 36 publications
(33 reference statements)
4
113
0
Order By: Relevance
“…Consistent with our findings in human islet beta cells, a previous in vitro study showed that synthetic hIAPP induces caspase-8 activation in rodent beta cells [42]. Interestingly, aggregates of amyloid beta peptide were also shown to induce caspase-8 activation and apoptosis in neural cells, probably via the Fas-mediated apoptotic pathway [43]. Moreover, active caspase-8 and Fas-positive cells have been reported in the brain in Alzheimer's disease [44,45].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings in human islet beta cells, a previous in vitro study showed that synthetic hIAPP induces caspase-8 activation in rodent beta cells [42]. Interestingly, aggregates of amyloid beta peptide were also shown to induce caspase-8 activation and apoptosis in neural cells, probably via the Fas-mediated apoptotic pathway [43]. Moreover, active caspase-8 and Fas-positive cells have been reported in the brain in Alzheimer's disease [44,45].…”
Section: Discussionsupporting
confidence: 91%
“…Early MD simulations of amyloidogenic peptides (5,25) consisting of U-shaped β-strandturn-β-strand peptides in the bilayer predicted ion-permeable channels formed by loosely attached mobile subunits with morphologies and dimensions similar to the AFM-images of amyloid channels (7,8). U-shaped motifs, first predicted by modeling of Aβ [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (26), appear as a general feature of amyloid organization, suggesting that other U-shaped amyloid organizations may also form dynamic ion channels in the fluidic membrane (8). Because N9 and p3 have membrane-spanning segments, we modeled their 3D structures in the bilayer using the previous successful protocol (5,25).…”
Section: Resultsmentioning
confidence: 99%
“…Because of their nonamyloidogenic nature, these peptides are assumed to be nonpathogenic and these pathways are even being targeted for AD therapeutics. Significantly, p3 peptides are present in AD amyloid plaques (17)(18)(19)(20), are the main constituent of cerebellar preamyloid lesions in Down syndrome (21) and induce neuronal toxicity (22)(23)(24). However, their biophysical properties, mechanism of toxicity, and pathological significance in AD and Down syndrome remain unclear.…”
mentioning
confidence: 99%
“…They demonstrated that A␤ and A␤ [25][26][27][28][29][30][31][32][33][34][35] induce apoptosis through caspase-dependent pathways. [41][42][43][44][45][46][47] In vivo, 1 week after A␤ [25][26][27][28][29][30][31][32][33][34][35] , an increase in caspase-3 activity in the hippocampus of rats 9 and increases in levels of pro-caspases 9, 12, and 3 in the hippocampus of mice 11 were observed. In the present study, we observed increases in pro-and cleaved forms for caspase-9 (mitochondrial stress marker) and caspase-12 (endoplasmic reticulum stress marker) in all structures except the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%